Powder metallurgy of Zn–Mn/CNF biodegradable composites: Role of ball milling and sintering on material performance - Yng, Yeak; Chan, Kar Fei; Abd Samad, Muhammad Izzuddin; Ramlee, Muhammad Hanif; Yaakob, Yazid; Tanemura, Masaki; Mohd Yusop, Mohd Zamri (Elsevier Ltd, 2025)
Zinc (Zn) alloys represent a promising category of biodegradable implant materials for bone fixation applications, eliminating the need for subsequent removal procedures. By combining zinc with other metals and carbonaceous materials, its mechanical strength and ductility are expected to improve. However, the formation and behavior of pores during manufacturing require an optimized configuration to ensure functional efficacy. This research aims to produce a carbon nanofiber-reinforced zinc-manganese (Zn–Mn/CNF) composite using powder metallurgical techniques. The impact of ball milling time and sintering method on the homogeneity, elemental distribution, and crystallography of Zn–Mn/CNF was assessed, along with its surface topography and microhardness. Micrograph analysis showed that the duration of ball milling influenced the porosity, microcracks, and oxide formation in the composites. After an extended ball milling period (60–120 min), the composite exhibited increased porosity and microcracking. Conversely, a 5-min milling reduced the crystallite size of the α-Zn phase to 77.4 nm with minimal oxidation. The sintered composite displayed lower Vickers hardness (39.44 HV) compared to its counterpart (41.26 HV). The limitations of the sintering parameters (400 °C for 1 h) failed to induce a phase transition from the primary α-Zn phase to any secondary phase with increased hardness. Furthermore, the sintering process increased the porosity about 4 % and enlarged the pore size, weakening the structure and reducing the composite's hardness. The synergistic effect of ball milling and sintering on the Zn–Mn/CNF composite has been examined in relation to its microstructural characteristics and microhardness performance. The optimal ball milling and sintering conditions for achieving high densification and surface hardness in the Zn–Mn/CNF composite are 5 min of ball milling without additional sintering.